The effects of salinity on the growth and some morphological and anatomical characters of Enteromorpha flexuosa(L) grev - Rohani Mohd Rose (Fakulti Pengajian Maritim dan Sains Marin, 2011)
In algal taxonomy, the identification of plants would depend on the selection of taxonomic characters which are stable under varying environmental conditions.